Saint Agnes by Manuel García “Hispaleto”: the image of the young female saint in nineteenth-century religious art in Spain - ANA BAEZA RUIZ (Boletín del Museo del Prado)
Taking as its starting point the little known painting Apparition of Saint Agnes to her parents by the Sevillian painter Manuel García “Hispaleto”, the article examines a series of interrelated historical complexities around gender and religion in mid-19th-century Spain, specifically with regard to models of femininity for girls and young women. Through a thematic and formal analysis, this study addresses the work in the context of contemporary religious, cultural and literary influences with the aim of expanding the ways in which we can read and interpret images from that period.